Multiple safety net regulators and agency problems in the EU: Is Prompt Corrective Action partly the solution? - Mayes, David G.; Nieto, María J.; Wall, Larry (Journal of Financial Stability, 2008)
Prompt Corrective Action (PCA) provides a more efficient mechanism for dealing with problem banks operating in more than one European country. In a PCA framework, a bank's losses are likely to be substantially reduced. This reduction in the losses to deposit insurance and governments will improve the problem of allocating those losses across the various insurance schemes and make it less likely that any deposit insurer will renege on its obligations in a cross-border banking crisis. This paper presents a stylized mechanism aimed at dealing with the cross-border agency problems that arise in supervising and resolving cross-border banking groups in the European Union (EU). The authors assume that PCA policies have been implemented by the national supervisors and explore the institutional changes needed in Europe if PCA is to be effective as an incentive compatible mechanism. The paper identifies these changes starting with enhancements in the availability of information on banking groups to supervisors. Next, the paper considers the collective decision making by supervisors with authority to make discretionary decisions within the PCA framework as soon as a bank of a cross-border banking group falls below the minimum capital standard. Finally, the paper analyzes the coordination measures that should be implemented if PCA requires the bank to be resolved.